Study neuropsycologic memory system in a sample of middle age adults with mixed anxiety-depression disorder - Sarria Joya, César (2017)
The objective of this research is to describe and analyze the memory system disorders of patients diagnosed with depression and/or anxiety, making a comparative study with a control group of people without dysfunction in this area affective-emotional ; and explain the commitment of its functional activity using the theoretical model informational (Ortiz, 1994,1995,1997, 1997b, 1998, 1999,2002). The sample consisted of all patients diagnosed by the clinical neuropsychologist , which have been referred for evaluation and treatment, in the Service of Neuropsychology of Hospital Edgardo Rebagliati ,and the control group was set up by subjects who do not submit such alteration, and that they are homogeneous in the demographic data with the clinical sample . We used the Busckhe Selective Memory of Herman and Paula Altman, adapted and validated in the middle by 1998 Llaja, V., 2000 in a sample of patients with transient global amnesia, and in children of 5 years respectively. Data were collected during the period January to Nov 2011-. The design was quasi-experimental design, with 2 groups according to the classification of Hernández, Fernández & Baptista (2010). Was administered in addition to the Zung Scale of Anxiety/Depression to determine the degree of dysfunction in the studied sample. It is also interpreted the findings through the Model TIP, which is demonstrating their validity in the comprehensive neuropsychological clinical study of these disorders.